Suspicious Categories and Diffuse Control in the Practice of the Family Judge (2018)
Introduction: In Mexico, from the Reform of June 10, 2011, the ex officio constitutional and conventional protective role is imposed on local family judges as a guarantee of human rights when identifying suspicious categories. These are understood as prohibited traits that undermine human dignity through differential treatment and that put certain stereotyped groups at a disadvantage for no reason. Such inequality may be caused by the legislator when determining an abstract assumption (formal inequality), or by practice when applying an abstract rule to a specific case (substantive inequality). Therefore, the present research aims to identify and take down such restrictions based on the principle of equality. Methods: The research problem is approached from legal realism, particularizing the study in specific cases with their relevant explanation. In addition, the comparative method is used to compare applicable laws. Results: It is necessary to identify and resolve conflicts in which suspicious categories are present so that the local family judge does not violate the principle of non-discrimination. Conclusions: There should be a distinction established between formal and substantial equalities, which will guarantee, on the part of the local judge, the protection of human dignity and the fight against disadvantage as non discriminatory assumptions in practice.